IMAN, RASIONALITAS, KEBENARAN DAN EKSISTENSI MANUSIA Sebuah Refleksi Filosofis Atas Ensiklik Fides et Ratio Paus Yohanes Paulus II - Ehaq, Timoteus Ata Leu (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2019)
Even though, the problem of the relationship between faith and reason has been a very classical topic in the history of philosophical and theological discussions, the urgency to keep on discussing the interrelationship between these two matters remains. The idea is that, at the core of the debates made of the connection of the two capacities, it is always concerned with the fundamemtal elements of human existence itself, which is, the problem of the sources of knowledge and understanding, truth, experience, understanding, knowledge and the fullness of human existence itself. This articles disucesses these points the document of Fides et Ratio implies. The idea is that, behind of John Paul II’s points of the relationship of these two, there are some philosophical elements which one can find and discuss. As previously mentioned, those ideas are the problem of truth and certainty, the status of reason and experience as the sources of knowledge, the problem of knowing and understanding, the problem of meaning and values and finally the problem of the fullness of human existence.